Analisis Penerapan Asas Kepentingan Militer dalam Pemberhentian dengan Tidak Hormat terhadap Prajurit TNI Pelaku Tindak Pidana Desersi - Titin Gusriyanti; Meysita Arrum Nugroho (Decisio: Jurnal Ilmiah Hukum, 2026)
This research is entitled "Analysis of the Application of the Principle of Military Interest in the Dishonorable Discharge of Indonesian National Armed Forces Soldiers Who Perpetrate the Crime of Desertion." The purpose of this research is to determine and analyze the provisions of laws and regulations that regulate the principle of military interest in the process of dismissing Indonesian National Armed Forces soldiers, as well as to examine the application of this principle in the decision or decision of dishonorable discharge of Indonesian National Armed Forces soldiers who commit the crime of desertion based on Indonesian positive law. This research uses a normative juridical method with a statute approach and a conceptual approach. The data used are sourced from primary legal materials in the form of applicable laws and regulations, as well as secondary legal materials such as literature, journals, and opinions of military law experts. The analysis is conducted descriptively qualitatively to interpret the relationship between the principle of military interest and its application in legal practice. The results of the research indicate that the principle of military interest is an important basis in determining the policy of dismissing Indonesian National Armed Forces soldiers in order to maintain discipline, honor, and the effectiveness of the military organization. However, the application of this principle must still pay attention to the principles of justice, proportionality, and protection of the rights of soldiers as citizens. Therefore, the implementation of dishonorable discharge against deserters needs to be carried out selectively and in a balanced manner so as not to result in violations of applicable legal values.